Development of Control Drainage Operation Model and Utilization Planning of Post-Fire Peatlands - Momon Sodik Imanudin; Bakri Bakri; M E Armanto; E Wildayana; S Al Rashid (Journal of Wetlands Environmental Management, 2021)
The research aimed to determine the monthly operational groundwater control and land use patterns in fire prevention efforts on peatlands. The research method was carried out using a detailed survey scale method in the representative sample area of 20-30 ha. Observations in the field included measuring the physical properties of soils and observing hydrological components. Group discussions with the community were conducted to explore information on the causes of fires, compilation of plans for operational activities in the field, and land use models. The research results showed that in the soil depth of 0-20 cm the level of peat maturity classified as Sapric (mature), at a depth of 20-50 cm is classified as hemic and at a depth of 50-100 cm belongs to fibric (immature). The effects of blocking canal construction were very significant in raising the water level in the channel and groundwater table. However, due to the low rainfall until December 2019, the groundwater level was not yet able to raise to the point of arrangement 40 cm. Till the end of December 2019, the groundwater level was at 70 cm, however there has been an increase in groundwater level of 30 cm since the beginning of December 2019. In the rainfall conditions < 2500 mm/year, blocking canal operations with a retention system have to begin in April. Agroforestry is the best model and Albizia chinensis (Osbeck) Merr. (sengon) in combination with pineapple plants are the best land use pattern. In addition, some short-term proposals are to provide infrastructure for firefighting, the construction of a road embankment, normalization of main rivers and canals, providing boring wells, making security control posts, training, monitoring, and providing some incentives for farmers to clear land and firefighting teams at the village level.